Factors Associated With Pneumonia In Toddlers At Sinjai Hospital - Eka Hadrayani; Khusnul Amalia Isman; Ilhamsyah; Muthahharah (Jurnal Life Birth, 2022)
Toddlers are children aged 12 months to 59 months. This period is important in the process of developmental growth and development of toddlers and is called the Golden Period. The unsuitable growth status of children under five can increase the risk of morbidity and mortality because this condition causes infectious diseases such as pneumonia to occur frequently in children under five known as pneumonia. Pneumonia in children under five is still a major health problem in the world. Other risk factors for pneumonia are nutritional status, exclusive breastfeeding, and immunization. This study aims to determine the factors associated with pneumonia in children under five at Sinjai Hospital in 2022. The research design used was a quantitative study with a cross-sectional approach. Researchers used a sampling technique, namely Non-Probability Sampling with a Purposive Sampling technique. The samples obtained were 48 using observation sheets. The results of this study using the chi-square test on the nutritional status variable obtained a p-value of 0.018 <0.05 which indicated that there was a relationship between nutritional status and pneumonia, the variable of exclusive breastfeeding with a p-value of 0.036 <0.05 there was a relationship between exclusive breastfeeding against pneumonia, while the immunization variable obtained a p-value of 0.010 <0.05 there was a relationship between immunization against pneumonia. The study concludes that there is a relationship between nutritional status, exclusive breastfeeding, and immunization against pneumonia. In Sinjai Hospital it is recommended to improve health promotion of nutrition for children under five, immunization programs, and exclusive breastfeeding to minimize the occurrence of pneumonia in children under five.